2021
DOI: 10.7150/thno.52677
|View full text |Cite
|
Sign up to set email alerts
|

Conditioned medium from adipose-derived stem cells attenuates ischemia/reperfusion-induced cardiac injury through the microRNA-221/222/PUMA/ETS-1 pathway

Abstract: Rationale: Cardiovascular diseases, such as myocardial infarction (MI), are the leading causes of death worldwide. Reperfusion therapy is the common standard treatment for MI. However, myocardial ischemia/reperfusion (I/R) causes cardiomyocyte injury, including apoptosis and fibrosis. We aimed to investigate the effects of conditioned medium from adipose-derived stem cells (ADSC-CM) on apoptosis and fibrosis in I/R-treated hearts and hypoxia/reoxygenation (H/R)-treated cardiomyocytes and the underly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 55 publications
0
24
0
Order By: Relevance
“…Antiapoptotic proteins Bcl-2, Bcl-x, and Bcl-w block the apoptotic cascade by inhibiting cytochrome C release [ 51 ]. Another study demonstrated that ADSC-CM can significantly reduce the expression of proapoptotic proteins such as Bax during ischemia-reperfusion-induced cardiac injury [ 52 ]. P53 directly activates Bax to permeabilize the mitochondrial membrane and initiate the apoptotic program [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Antiapoptotic proteins Bcl-2, Bcl-x, and Bcl-w block the apoptotic cascade by inhibiting cytochrome C release [ 51 ]. Another study demonstrated that ADSC-CM can significantly reduce the expression of proapoptotic proteins such as Bax during ischemia-reperfusion-induced cardiac injury [ 52 ]. P53 directly activates Bax to permeabilize the mitochondrial membrane and initiate the apoptotic program [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…The animals were anesthetized and decapitated, and brains were collected. The brain sample was embedded in paraffin, coronally sliced at 5-μm, and measured by HE staining ( Zhang L. et al, 2021 ), and terminal deoxynucleotidyl transferase (TdT)-mediated dUTP nick-end labeling (TUNEL) staining ( Lee et al, 2021 ). The areas around five randomly selected injury sites were quantified.…”
Section: Methodsmentioning
confidence: 99%
“…Knockout of miR-221/222 in mice increased apoptosis and fibrosis; however, treatment with conditioned medium from adipose-derived MSCs decreased apoptosis and fibrosis [ 93 ]. Lee et al found that intramuscular injection of conditioned media from adipose-derived MSCs attenuates ischemia in mice [ 94 ]. Taken together, exosomes from adipose-derived stromal cells ameliorated ischemia through the action of miR-221/222.…”
Section: Somatic Stem Cellsmentioning
confidence: 99%